Figure of Sadashivamurti or Maheshmurti - Temples of India Project Team (Jio Institute, 2024)
Sadashivamurti or Maheshmurti, a detailed view of the presiding deity in the garbhagriha (sanctum sanctorum) ) of the Sadashiva Temple (Temple 5), Baroli group of temples.